Implementasi Manajemen Aset dan Liabilitas Dalam Mengelola Risiko Likuiditas pada Bank Syariah Indonesia - Rahma Septiani Adillah; Muthia Ghassanie Julaeha; Tina Lailasari; Yani Aguspriyani (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to examine the implementation of Asset and Liability Management (ALMA) in managing liquidity risk at Bank Syariah Indonesia (BSI). The background of this research is based on the structural challenges faced by Islamic banking in managing liquidity, particularly following the merger of three state-owned Islamic banks in 2021, which established BSI as the largest Islamic bank in Indonesia. The method used in this study is a qualitative approach through library research. The data were obtained from BSI’s financial reports for the 2021–2024 period, regulations issued by Bank Indonesia and the Financial Services Authority (OJK), as well as various recent scientific literature. The results of the analysis indicate that BSI implements ALMA through four main mechanisms: (1) managing the maturity matching of assets and liabilities; (2) utilizing Sharia-based liquidity instruments such as SBIS and FASBIS; (3) conducting stress testing and cash flow projections; and (4) strengthening the internal control system through the ALCO committee. Following the merger, BSI’s Non-Performing Financing (NPF) ratio decreased from 2.93% in 2021 to 1.97% in 2024, reflecting an improvement in asset quality as well as liquidity stability. However, this study also identifies several challenges, including the limited availability of instruments in the Islamic money market and the complexity of managing third-party funds based on profit-sharing schemes. Overall, the study concludes that the effective implementation of ALMA plays a significant role in enhancing BSI’s liquidity resilience and serves as a fundamental basis for the sustainability of Islamic banking operations in Indonesia.